The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/10946705231175937
|View full text |Cite
|
Sign up to set email alerts
|

Pushing Forward the Transition to a Circular Economy by Adopting an Actor Engagement Lens

Katrien Verleye,
Arne De Keyser,
Néomie Raassens
et al.

Abstract: Circular business models (CBMs), such as product-service systems, are rapidly gaining traction in light of a transition to a more circular and sustainable economy. The authors call for a new approach to inform and guide the development and adoption of these CBMs. The main reason is that different actors in the service ecosystems or networks linked to these business models—such as firms, customers, and governmental bodies—may be reluctant to join or even impede the transition to a circular economy. Based upon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…An aim of service ecosystems should therefore be to reduce consumption and exploitation of limited natural resourcesas well as to develop resilience to damage to these resources such as climate change (Field et al, 2021). This is aligned with a circular business models perspective that close resource loops and reduce the burden on natural resources (Verleye et al, 2023).…”
Section: The Evolving Conception Of Service and Naturementioning
confidence: 99%
“…An aim of service ecosystems should therefore be to reduce consumption and exploitation of limited natural resourcesas well as to develop resilience to damage to these resources such as climate change (Field et al, 2021). This is aligned with a circular business models perspective that close resource loops and reduce the burden on natural resources (Verleye et al, 2023).…”
Section: The Evolving Conception Of Service and Naturementioning
confidence: 99%
“…The authors argue that sharing businesses can realize their economic and circular potential by engaging customers. This is further discussed in an article in the Journal of Service Research by Verleye et al (2023), zooming in on circular business models and actors (customers, firms, public service providers and governmental bodies) being reluctant to join the transition to circularity. The authors theorize about how to achieve "circular economy engagement" and highlight motivation-related, opportunity-related and ability-related practices.…”
Section: Circularity In Service Researchmentioning
confidence: 99%
“…However, aside from a few notable exceptions (e.g. De Bruyne and Koskela-Huotari et al, 2023;Verleye et al, 2023), few articles with an explicit focus on circularity can be found in service journals. Research on the sharing economy, for example, does not focus on its circularity principles (see Henry et al, 2021 for an overview), while many customers do not put in their best effort to maintain the shared resources (such as cars or bikes), challenging resource lifecycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They formulate a research agenda for CE ecosystems. Verleye et al, 2024 use an abductive analysis of circular business model papers to develop theories to achieve CE engagement. They identify specific strategies and provide illustrative cases for each.…”
Section: The Special Issuementioning
confidence: 99%